The Effect of Premium Income, Claim Payment, Risk-Based Capital, Investment Return, and Underwriting Result on The Profits of Insurance Companies Listed on The Indonesia Stock Exchange For The 2015-2018 Period - Wahyono Wahyono; Nurochim Nurochim; Indarti Diah Palupi (Riset Akuntansi dan Keuangan Indonesia, 2021)
This study aims to determine the effect of premium income, claim payments, risk based capital, investment returns and underwriting results on the profits of insurance companies listed on the Bursa Efek Indonesia (BEI) for the 2015-2018 period. The analysis technique used is panel data regression with the Common Effect Model, Fixed Effect Model and Random Effect Model. The results of this study indicate that premium income, claim payments, and investment returns have an effect on profits. Meanwhile, risk based capital and underwriting results have no effect on profits.